2021
DOI: 10.5603/gp.a2021.0014
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and opinions of patients and medical staff about patients’ rights

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…The conclusions of this study align with previous research findings, demonstrating a high level of awareness among nursing staff concerning patients' rights (Arbabisarjou et al, 2016;Czajkowska et al, 2021;Ashour et al, 2022;Alwani et al, 2020;Manik et al, 2021 (Ghanem, 2015;Mpouzika et al, 2021;Özdemir & Erenoğlu, 2021). Our findings emphasize the need for targeted educational initiatives for nursing staff to address identified knowledge gaps.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The conclusions of this study align with previous research findings, demonstrating a high level of awareness among nursing staff concerning patients' rights (Arbabisarjou et al, 2016;Czajkowska et al, 2021;Ashour et al, 2022;Alwani et al, 2020;Manik et al, 2021 (Ghanem, 2015;Mpouzika et al, 2021;Özdemir & Erenoğlu, 2021). Our findings emphasize the need for targeted educational initiatives for nursing staff to address identified knowledge gaps.…”
Section: Discussionsupporting
confidence: 90%
“…The outcomes of these studies have revealed a range of levels of awareness. Certain studies have reported a positive or elevated level of awareness and knowledge regarding patients' rights among nurses (Arbabisarjou et al, 2016;Czajkowska et al, 2021;Ashour et al, 2022;Lebda et al, 2022;Arbabisarjou et al, 2016;Sheikhtaheri et al, 2016;Eldawlatly & Alohali. 2018;Demirsoy & Kirimlioglu, 2016;Mpouzika et al, 2021;Czajkowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…4 Patients' rights are influenced by the patient's status, family, society, and country-related factors. 5 Human rights and nurses' roles have focused on the values embodied in the code of ethics developed by the Indian Nursing Council. 6 Patients' rights vary from one country to another and from jurisdiction to others, often depending upon prevailing cultural and social norms.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the patients’ bill of rights is considered a guide to choosing and ensuring the best future decisions that attain the patients’ benefits and can be the starting point for comprehensive interest in patients’ rights and a correct definition of the relationship between healthcare receivers and providers [ 5 ]. Patients’ rights may vary by country, authority, and cultural and social norms [ 6 ], but they guarantee proper services, patient independence and decision-making rights, privacy, and access to a complaint system [ 7 ]. It also improves patient satisfaction; reduces treatment costs, hospital stays, and irreversible physical or emotional harm; and allows patients to participate in the treatment plan [ 5 ].…”
Section: Introductionmentioning
confidence: 99%